Unsaturated fatty acids incorporated in HDL in hypo- and hyperalphalipoproteinemia--relation to the HDL-cholesterol level - Večeřa, Rostislav; Chmela, Zdeněk; Hřebíček, Jiří; Skottová, N (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1994)
Proportions of unsaturated fatty acids of high density lipoprotein (HDL) lipids and their relationships to the HDL-cholesterol level were compared in hypo- and hyperalphalipoproteinemic subjects. Both groups did not differ in the level of serum cholesterol. However, hypoalphalipoproteinemia was associated with hypertriglyceridemia, higher HDL-triacylglycerol level, and higher proportion of HDL-18:1 (oleic acid) and lower proportions of HDL-18:2 (linoleic acid) and 20:4 (arachidonic acid) than hyperalphalipoproteinemia. The HDL-20:4 was the only fatty acid correlating (negatively) with HDL-cholesterol. However, HDL-18:1 correlated positively and HDL-18:2 negatively with HDL-triacylglycerols, lipids related to the fall of HDL-cholesterol. These results suggest 1) an antagonism of 20:4 and 18:2 as structural components of HDL lipids in relation to the HDL-cholesterol level, and 2) an association of replacement of HDL 18:2 by 18:1 with the disorder of plasma triacylglycerol metabolism.
Keywords: lipoproteiny HDL; Male; ženské pohlaví; Cholesterol, HDL; Hypolipoproteinemias; Humans; Middle Aged; lidé; Female; Hyperlipoproteinemias; Fatty Acids, Nonesterified; mužské pohlaví; Lipoproteins, HDL; lidé středního věku; HDL-cholesterol; hypolipoproteinemie; kyseliny mastné neesterifikované; hyperlipoproteinemie